2005
DOI: 10.1074/jbc.m505659200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-dependent Syntaxin-4 and SNAP-23 Clustering Regulates Caveolar Fusion with the Endothelial Plasma Membrane

Abstract: We determined the organization of target (t) SNARE proteins on the basolateral endothelial plasma membrane (PM) and their role in the mechanism of caveolar fusion. Studies were performed in a cellfree system involving endothelial PM sheets and isolated biotinlabeled caveolae. We monitored the fusion of caveolae with the PM by the detection of biotin-streptavidin complexes using correlative high resolution fluorescence microscopy and gold labeling electron microscopy on ultrathin sections of PM sheets. Imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 22 publications
7
85
0
8
Order By: Relevance
“…Interestingly, STED microscopy revealed that the individual area of clusters was almost identical in CHOwt and CHO-A6 cells (145 ± 35 nm, syntaxin-4; 136 ± 30 nm, SNAP23). These findings correspond to similar electron microscopy data obtained from endothelial cells (Predescu et al , 2005; Figure 2, E–H). Together, results from TIRF and STED microscopy strongly suggest that CHO-A6 cells not only have fewer cholesterol-dependent SNARE clusters in the PM but also that these clusters appear to contain a lower density of molecules per cluster.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, STED microscopy revealed that the individual area of clusters was almost identical in CHOwt and CHO-A6 cells (145 ± 35 nm, syntaxin-4; 136 ± 30 nm, SNAP23). These findings correspond to similar electron microscopy data obtained from endothelial cells (Predescu et al , 2005; Figure 2, E–H). Together, results from TIRF and STED microscopy strongly suggest that CHO-A6 cells not only have fewer cholesterol-dependent SNARE clusters in the PM but also that these clusters appear to contain a lower density of molecules per cluster.…”
Section: Resultssupporting
confidence: 91%
“…SNAP23 and syntaxin-4 have been implicated in caveolin transport and/or caveolae functioning (Predescu et al , 2005; Choudhury et al , 2006). As CHO-A6 cells are characterized by 1) reduced cholesterol levels in DRMs (Figure 3C) and the PM (Cubells et al , 2007), 2) cholesterol-dependent caveolin retention, and 3) increased amounts of SNAP23/syntaxin-4 in crude Golgi membranes (Figure 3A), we reasoned that SNAP23 and syntaxin-4 could be accumulating in the Golgi of CHO-A6 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other SNAREs that might be involved are SNAP23, a ubiquitous Q-SNARE active in a large number of other exocytoses, regulated and constitutive (e.g. Bao et al, 2008;Castle et al, 2002;Feng et al, 2002;Predescu et al, 2005;Puri and Roche, 2006;Reales et al, 2005;Wang et al, 2007), and Stx6, another Q-SNARE, also known to operate in the TGN, in which it appears to interact with VAMP4 (Katsumata et al, 2007;Steegmaier et al, 1999;). In the case of these two Q-SNAREs, however, the mechanism of involvement in enlargeosome exocytosis, whether direct or indirect, is still undefined.…”
Section: Introductionmentioning
confidence: 99%